If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + m + -7m = -2 Reorder the terms: m + -7m + 2n = -2 Combine like terms: m + -7m = -6m -6m + 2n = -2 Solving -6m + 2n = -2 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2n' to each side of the equation. -6m + 2n + -2n = -2 + -2n Combine like terms: 2n + -2n = 0 -6m + 0 = -2 + -2n -6m = -2 + -2n Divide each side by '-6'. m = 0.3333333333 + 0.3333333333n Simplifying m = 0.3333333333 + 0.3333333333n
| 5/6=-1/8x | | 1/3x2-4=21 | | 7x^2+6xy-y^2=0 | | 4(x+6)-3x=-2x+2-8 | | 0.7x-33.33=x+7 | | 11a-b+3a-(-7b)= | | w^2-3w-1890=0 | | 12x^2-(4x-3)(3x+1)=-2 | | 4(x-4)+2x=3(x-2)+5 | | 0.75x-33.3=x+7 | | U=23(6)+240 | | 3x-x=15 | | U=23n+240 | | 6x+9-7x-14=0 | | -3t(t-1)=2t+6 | | 2/2x-5/6x | | U=14n+9n+231+9 | | (8x^5)/(3)-(7x^3)/(6) | | s/616 | | -9h+15=27-2h | | 76-4x=7x-21 | | 6m-7n^5/3m^3*n^3 | | 1/3×21 | | 10x+8(x-3)-8= | | -6(x-1)-7=-7x+7 | | 10.8a+9.8a-7.9=-7.6 | | (x+6)((2x-1)(x+6))=0 | | (3b-4)(6b+5)-2= | | x=4/3×3.14×7^3 | | -14a+9=11a+12 | | 4/7=2c | | 2n+b-3n=-6 |